Behavior of Reinforced Reactive Powder Concrete Two-Way Slabs under Static and Repeated Load - Hamid, Hala Aqeel; Mohammed, Shatha D. (Civil Engineering Journal, 2018)
This paper studies the behavior of reinforced Reactive Powder Concrete (RPC) two-way slabs under static and repeated load. The experimental program included testing six simply supported RPC two-way slabs of 1000 mm length, 1000 mm width, and 70 mm thickness. All the tested specimens were identical in their material properties, and reinforcement details except their steel fibers content. They were cast in three pairs, each one had a different steel fibers ratio (0.5 %, 1 %, and 1.5 %) respectively. In each pair, one specimen was tested under static load and the other under five cycles of repeated load (loading-unloading). Static test results revealed that increasing steel fibres volume fraction from 0.5 % to 1 % and from 1% to 1.5%, led to an increase in the: first crack load by (32.2 % and 52.3 %), ultimate load by (36.1 % and 17.0 %), ultimate deflection by (33.6 % and 3.4 %), absorbed energy by (128 % and 20.2 %), and the ultimate strain by (1.1 % and 6.73 %). It also increased the stiffness and the ductility of the specimens especially at the final stages of loading. Additionally, it delayed the propagation of the cracks, controlled their growth, kept the integrity of the specimens at post cracking stage, and avoided their ruin at the failure stage through its â€œbridgingâ€ effect. For the repeated load test, applying five cycles of repeated load to the steel fiber reinforced RPC two-way slab specimens led to a decreasing in the ultimate load capacity, ultimate deflection, ultimate strain, and absorbed energy in a comparison with the corresponding static test specimens, and that because of the loading-unloading process which causes a fluctuation of stresses and more damages in concrete. Increasing the steel fibers volume fractions decreased the dissipated energy of the specimens that subjected to a repeated load, where the difference percent of dissipated energy between the first and second cycles of (R0.5 %, R1 %, and R1.5 %) specimens were (68.0 %, 46.2%, and 32.4%) respectively.